Subchondral Pathology: Proceedings of the International Consensus Meeting on Cartilage Repair of the Ankle - Yoshiharu Shimozono (2018)
© 2018, The Author(s) 2018. Background: The evidence supporting best practice guidelines in the field of cartilage repair of the ankle are based on both low quality and low levels of evidence. Therefore, an international consensus group of experts was convened to collaboratively advance toward consensus opinions based on the best available evidence on key topics within cartilage repair of the ankle. The purpose of this article is to report the consensus statements on “Subchondral Pathology” developed at the 2017 International Consensus Meeting on Cartilage Repair of the Ankle. Methods: Seventy-five international experts in cartilage repair of the ankle representing 25 countries and 1 territory were convened and participated in a process based on the Delphi method of achieving consensus. Questions and statements were drafted within 11 working groups focusing on specific topics within cartilage repair of the ankle, after which a comprehensive literature review was performed and the available evidence for each statement was graded. Discussion and debate occurred in cases where statements were not agreed upon in unanimous fashion within the working groups. A final vote was then held, and the strength of consensus was characterized as follows: consensus, 51% to 74%; strong consensus, 75% to 99%; unanimous, 100%. Results: A total of 9 statements on subchondral pathology reached consensus during the 2017 International Consensus Meeting on Cartilage Repair of the Ankle. No statements achieved unanimous support, but all statements reached strong consensus (greater than 75% agreement). All statements reached at least 81% agreement. Conclusions: This international consensus statements regarding subchondral pathology of the talus derived from leaders in the field will assist clinicians in the assessment and management of this difficult pathology.